VD_FINDINFO HC / 2012 / 438 vom 4. Juni 2012 - VD Tribunal cantonal (2012)
RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL, INDEMNITÉEN GÉNÉRAL, RÉINTÉGRATION PROFESSIONNELLE | 337c CO, 59 LPers-VD, 60 LPers-VD, 61 LPers-VD